Exploration of Copper(II) Acetate Catalyzed Regioselective Ethoxylation of o-Haloanilides with Picolinamide as a Directing Group - Li, Xiaoyi; Qin, Dingmei; Li, Yanping; Mao, Zewei (Synlett, 2022)
An efficient Cu-catalyzed Ullmann-type C–O coupling of o-haloanilides was developed. This method permits regioselective 2-ethoxylation of N-(2-bromoaryl)- or N-(2-iodoaryl)picolinamides in ethanol with Cu(OAc)2 as a convenient catalyst and with picolinamide as a directing group and intramolecular ligand. The reaction is characterized by good regioselectivity, high yields, and the absence of the need for an additional ligand.
Keywords: copper catalysis; Ullmann coupling; ethoxylation; haloanilides; picolinamides